Case Report: Indocyanine Green-Based Angiography for Real-Time Assessment of Superficial Brachialis Axial Pattern Flap Vascularization in Two Dogs - Michalik, David; Nolff, Mirja Christine (Frontiers in Veterinary Science, 2022)
This case report describes the method and feasibility of near infrared angiography (NIRA) to improve the surgical procedure of two superficial brachial axial pattern flaps intraoperatively using two camera systems. Two client-owned dogs were treated for tumors on their antebrachia with wide surgical excision. The defects were closed with a superficial brachial flap in both cases. A different NIRA camera system was used in each case to identify the perforator vessel and flap margins accordingly. Case 1 developed a seroma and healed without further complications. Case 2 developed partial flap necrosis, underwent revision surgery, and healed by secondary intent. NIRA proved useful intraoperatively in identifying the perforator vessel and determining flap margins. As these are only two cases, caution should be used in extrapolating the results.